Role of the hedgehog signaling pathway in rheumatic diseases: An overview - Su, Yazhen; Xing, Hao; Kang, Jie; Bai, Linkun; Zhang, Liyun (Frontiers in Immunology, 2022)
Hedgehog (Hh) signaling pathway is an evolutionarily conserved signal transduction pathway that plays an important regulatory role during embryonic development, cell proliferation, and differentiation of vertebrates, and it is often inhibited in adult tissues. Recent evidence has shown that Hh signaling also plays a key role in rheumatic diseases, as alterations in their number or function have been identified in rheumatoid arthritis, osteoarthritis, ankylosing spondylitis, systemic sclerosis, and Sjogren's Syndrome. As a result, emerging studies have focused on the blockade of this pathogenic axis as a promising therapeutic target in several autoimmune disorders; nevertheless, a greater understanding of its contribution still requires further investigation. This review aims to elucidate the most recent studies and literature data on the pathogenetic role of Hh signaling in rheumatic diseases.